2012
DOI: 10.1681/asn.2012020119
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Neutrophil Interactions in ANCA-Associated Diseases

Abstract: The two salient features of ANCA-associated vasculitis (AAV) are the restricted microvessel localization and the mechanism of inflammatory damage, independent of vascular immune deposits. The microvessel localization of the disease is due to the ANCA antigen accessibility, which is restricted to the membrane of neutrophils engaged in b2-integrin-mediated adhesion, while these antigens are cytoplasmic and inaccessible in resting neutrophils. The inflammatory vascular damage is the consequence of maximal proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 139 publications
0
61
0
1
Order By: Relevance
“…(Halbwachs and Lesavre, 2012;Gaffo, 2013). Small vessel vasculitis classification includes microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis, and granulomatosis with polyangiitis.…”
Section: Introductionmentioning
confidence: 99%
“…(Halbwachs and Lesavre, 2012;Gaffo, 2013). Small vessel vasculitis classification includes microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis, and granulomatosis with polyangiitis.…”
Section: Introductionmentioning
confidence: 99%
“…In severe sepsis, platelets are able to trigger the formation of neutrophil extracellular traps (NETs), which bind and clear pathogens [3]. ANCA-associated vasculitis (AAV) encompasses a variety of autoimmune diseases characterized by the presence of Anti-Neutrophil Cytoplasmic Antibodies (ANCA) associated with small vessel damage [4,5]. Platelets and leukocytes co-localize and interact at sites of vessel injury, haemorrhage, thrombosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Zachem et al demonstrated, using a concanavalin A injection model (immune complex-induced GN model), that after the deposition of immune complexes, platelets adhere to glomerular endothelial cells and are activated to express P-selectin, mediating neutrophil accumulation and a subsequent inflammatory response (17). In the presence of ANCA, the inflammatory reaction triggered by activated neutrophils is intensified (18). Thus, persistent immune complex deposition could synergistically work with ANCA to aggravate intraglomerular inflammation, and this might explain the severity of proteinuria and renal dysfunction seen in ANCA-associated crescentic GN with immune deposits.…”
Section: Discussionmentioning
confidence: 99%